Consumo de marihuana y su asociación con los problemas reproductivos - Cardona Maya, Walter D; Muñoz Monsalve, Laura Valentina; Gómez Velásquez, Juan Carlos; Guerra Bustamante, Diana María; Duque Restrepo, Clara María (Revista Médica de Risaralda, 2023)
N/A